Comorbidity thyrotoxicosis with coronary heart disease - Khusainova, Munira Alisherovna (Science and Education, 2023)
Objective: to evaluate the effect of thyrostatics on clinical symptoms, the frequency of cardiac arrhythmias and morpho-functional parameters of the left heart in patients with a combination of thyrotoxicosis and ischemic heart failure. Materials and methods: 51 patients participated in the study. Group I - patients with CHF of functional class II-III (FC) on the background of coronary heart disease and concomitant thyrotoxicosis (n=24), average age - 58.6±4.6 years; group II - patients with manifest thyrotoxicosis without cardiovascular pathology (n=27), average age - 46.7±4.1 years. When included in the study and after 6 months of therapy with the addition of thyrostatics, the clinical condition of patients and physical activity were evaluated, daily monitoring of an electrocardiogram and an echocardiographic study (EchoCG) were performed. Results: after 6 months of combined therapy with the inclusion of thyrostatics against the background of achieved persistent drug-induced euthyroidism in comorbid patients (group I), tolerance to physical exertion increased (p <0.001), the severity of clinical symptoms of CHF decreased, the frequency of cardiac arrhythmias significantly decreased (p <0.05). The analysis of the dynamics of EchoCG results in group I patients revealed a significant increase in the shock ejection index (p=0.04), left ventricular ejection fraction (p=0.01), shock volume (p=0.03), a decrease in the value of myocardial stress (p=0.02) and parameters characterizing the trans-mitral flow (E/A, p <0.05), which allowed us to judge the improvement of systolic and diastolic function of the left ventricle (LV) in the conditions of drug compensation for thyrotoxicosis. Conclusion: the inclusion of thyrostatics in the combination therapy and normalization of thyroid function contributed to the reduction of clinical symptoms of heart failure, the frequency of heart rhythm disturbances, improvement of systolic and diastolic LV function in comorbid patients with ischemic CHF and concomitant thyrotoxicosis.